2017
DOI: 10.1002/adfm.201606619
|View full text |Cite
|
Sign up to set email alerts
|

Injectable and Tunable Gelatin Hydrogels Enhance Stem Cell Retention and Improve Cutaneous Wound Healing

Abstract: Stem cells have shown substantial promise for various diseases in preclinical and clinical trials. However, low cell engraftment rates significantly limit the clinical translation of stem cell therapeutics. Numerous injectable hydrogels have been developed to enhance cell retention. Yet, the design of an ideal material with tunable properties that can mimic different tissue niches and regulate stem cell behaviors remains an unfulfilled promise. Here, an injectable poly(ethylene glycol) (PEG)-gelatin hydrogel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(159 citation statements)
references
References 66 publications
3
156
0
Order By: Relevance
“…[ 4b,23 ] The shear force can often damages the cells. [ 24 ] Previous studies revealed that hydrogels with shear thinning properties can protect the cells from the damage during injection, improving the viability of MSCs at wound sites. [ 6,25 ] To evaluate the protective effect of the SFN hydrogels, the cell‐free SFN‐LP hydrogels were injected (14 G needles) and the size of the LPs were measured after injection.…”
Section: Resultsmentioning
confidence: 99%
“…[ 4b,23 ] The shear force can often damages the cells. [ 24 ] Previous studies revealed that hydrogels with shear thinning properties can protect the cells from the damage during injection, improving the viability of MSCs at wound sites. [ 6,25 ] To evaluate the protective effect of the SFN hydrogels, the cell‐free SFN‐LP hydrogels were injected (14 G needles) and the size of the LPs were measured after injection.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] However, the state-of-the-art technology suffers from particular properties of conductive polymers, such as high hydrophobicity and insolubility, resulting in low adherence to wet substrates and poor penetration into living tissues. [18][19][20] To incorporate new functions to a conductive polymer for biomedical utilities, there are several limits of "add-on" approach because it does not alter the intrinsic properties of the electroconductive hydrogel network. [17] Moreover, a soft conductive adhesive, which can be utilized as injectable material, as well as bio-ink for in situ bioprinting, will close the gap between electroconductive materials and biomaterials, lead to numerous medical and clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…They have attracted considerable attention from chemists, materials and biomedicine scientists owing to their myriads of potential applications in many fields including tissue engineering, wearable devices, soft electronics, battery binders, etc. Among these versatile materials, self‐healing hydrogels, which can recover their original properties through autonomous healing after suffering from damages, exhibit an enormous potential in the fields of wound closure, scaffolds for tissue engineering, drug/cell delivery devices, and so on.…”
Section: Introductionmentioning
confidence: 99%